It Is Complicated: The Medico-Social Journey of an Undocumented Pregnant Adolescent - Helen Kest; Ashlesha Kaushik; Bushra Tehreem; David Goldberg (Hindawi Limited, 2020)
Adolescent pregnancies are a global health problem with over 16 million children born to this age group globally. Adolescent females also represent almost half of all adolescent global migrants. Adolescent pregnancy by itself is associated with poor health care access and morbidities; the additional risk of social insecurity in the case of undocumented adolescent migrants leads to higher risks for the mother and newborn. According to the CDC, adolescents comprise half of all new sexually transmitted diseases (STDs) including reported primary and secondary syphilis. Our case highlights the relationship between social insecurity for the undocumented adolescent migrant and excess risks for preventable mother-to-child transmission of communicable diseases. In formulating preventive measures and policies for the recent rise in sexually transmitted maternal diseases with resultant congenital infections, there is need for health care systems and providers to familiarize themselves with advocacy and other useful resources that will promote health care access for undocumented and other vulnerable adolescents. Additionally, local providers who work in areas with a large population of immigrant adolescents should utilize the untapped resources of these adolescents to develop youth community advocacy projects that link adolescents to health resources, including reproductive health.